Validation of single nucleotide polymorphism trait-markers and characterization of biofortified cassava (Manihot esculenta Crantz) - Ogungbesan, A.O. (Ladoke Akintola University of Technology, 2024)
Cassava (Manihot esculenta Crantz) is a vital industrial and staple crop in Sub-Saharan Africa (SSA) where it is valued for food security and consumer acceptability. Consumers with preference for white-fleshed cassava that lack Pro-vitamin A are prone to diseases associated with vitamin A deficiency. Biofortified cassava has great nutritional benefits in addressing micronutrient deficiency in resource-poor households. However, lack of adequate genomic information on local genetic resources has impeded the efficient conservation and improvement of biofortified cassava. The objectives of this study were to characterize 376 cassava accessions using Single Nucleotide Polymorphism (SNP) markers and to validate trait markers linked to Total Carotenoid Content (TCC), Dry Matter Content (DMC), and resistance to Cassava Mosaic Disease (CMD) for marker-aided selection in biofortified cassava breeding pipeline. In this study, 376 cassava accessions from three breeding programmes (International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria, International Center for Tropical Agriculture, CIAT-Cali, and the University of Hawaii, USA – the origins) were phenotyped and genotyped to achieve the study objectives. The cassava accessions were selected from the clonal evaluation trial (219), elite parents (108), advanced yield trial (30), high-priority genotypes (14), and released biofortified varieties (3) established at IITA-Ibadan, Nigeria. The accessions were phenotyped for resistance to Cassava Mosaic Disease (CMD), Total Carotenoid Content (TCC), and Dry Matter Content (DMC). The accessions were also genotyped with Kompetitive allele-specific primer procedure using 46 SNP markers comprising 36 quality control and 10 traits-linked markers. Phenotypic data were subjected to descriptive statistics, normality tests, and trait relationships. Genotypic data were subjected to population structure, phylogenetic analysis, and F-statistics. Marker validation was done using the Kruskall-Wallis test. The mean performance of the color chart score was 3.37 with total carotenoid content being 10.83μg/g fresh weight basis. The average percent dry matter content was 34.31% while for cassava mosaic disease severity recorded was 1.5. Further results revealed a significant negative correlation between TCC and DMC (-0.64**), and CMD (-0.18**). Twenty-eight accessions combined lower than mean population CMD severity score, high DMC (>30%), and high TCC (>15μg/g). Genotyping results showed that the highest expected heterozygosity (He= 0.493) was found in the genotypes that originated from Hawaii which was comparable to genotypes from IITA breeding programmes (He= 0.43). The Principal Component Analysis (PCA) and hierarchical clustering revealed two genetic sub-populations within the 376 cassava genotypes with accessions connected to the accession origins. The analysis of molecular variance results based on origin and sub-population revealed higher genetic variations in accessions within origin and subpopulations than among origin and subpopulations. The CMD three resistance markers, one DMC marker, and the three PVA markers showed a good predictive ability indicating their usefulness in cassava forward breeding programmes. These results showed a high level of genetic variation among cassava accessions with good levels of prediction for the CMD, DMC, and PVA markers tested in this study. This will facilitate the incorporation of marker-assisted selection in accelerating the improvement for these traits.